A distributed token based h-out of-k Mutual Exclusion protocol for mobile ad hoc networks. (27th January 2010) - Bencha?ba, Mahfoud; Ahmed Nacer, Mohamed
This paper describes a new distributed token based h-out of-k Mutual Exclusion (h-k-ME) protocol for mobile ad hoc networks. This protocol uses neither the routing layer nor a logical structure and agrees requests based on their distances to the token, their ages and their resources numbers. A request is sent within a dynamical radius computed so as to reach a part of nodes. The protocol is fault tolerant and manages one token with k resources in each partition. The mobility has little effect on the protocol's performances especially for medium and heavy loads.